Neonatal thrombocytopenia and associated factors - Sodha, Nandini; Nigam, Nehil; Kela, Gunjan (International Journal of Contemporary Pediatrics, 2021)
Background: The aim is to study neonatal thrombocytopenia and associated factors and compare the results with recent studies in neonates with thrombocytopenia admitted in neonatal intensive care unit (NICU). Methods: After taking detailed consent from parents/guardians, detailed maternal obstetrics and neonatal history were taken and complete physical examination was done and details of the investigations done and outcome was noted and evaluated. Relevant data was entered in the predesigned proforma and was analyzed. Immediate outcome was assessed by outcome or death. Results: The most common cause of neonatal thrombocytopenia was preterm gestational age. There were 68 (27.2%) neonates in the age group 28-32 weeks, 107 (42.8%) were in the age group 32-37 weeks and 75 (27.2%) were in the age group 37-42 weeks. Majority of the neonates were in the age group 32-37 weeks. We assessed outcome which was as follows, 98 (39.2%) neonates had expired and 152 (60.8%) neonates had survived in our study. Conclusions: We studied the etiology of neonatal thrombocytopenia and associated factors. The most common cause of neonatal thrombocytopenia found was preterm gestational age. The most common type of neonatal thrombocytopenia found in our study was moderate to severe thrombocytopenia. In our study, there was 39.6% was neonatal death rate. In our study, neonatal thrombocytopenia was associated with the following factors gestational age, intrauterine growth retardation, pre-eclampsia, multiple pregnancy, eclampsia, birth asphyxia, x-ray chest/abdomen, ultrasonography (USG) abdomen, USG cranium, liver function tests and renal function tests.